A CONTRASTIVE STUDY OF COMPLIMENTS IN ENGLISH AND UZBEK LANGUAGES (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the linguistic and cultural features of compliments in English and Uzbek languages. Compliments are regarded as important pragmatic tools that maintain positive relationships and express admiration or approval. The study explores similarities and differences in the structure, semantics, and pragmatic use of compliments in both languages. It also highlights how cultural norms shape the way compliments are expressed and responded to in English and Uzbek societies.